MAPbI3 nanowires prepared by a facile vapor transfer method for simple photodetector. (March 2020) - Hsieh, Rong-Hsuan; Liu, Yitong; Feng, Kejie; Mo, Xiaoliang
Highlights: A self-assembled method for PbI2 nanowires. A novel MAPbI3 nanowires synthesis method with good crystallization and morphology. The fabrication of MAPbI3 nanowires photodetector and the characterization. Abstract: MAPbI3 nanowires have become one of the promising materials for optoelectronic devices. Herein, a simple template-free vapor transfer approach to synthesize MAPbI3 nanowires on various substrates for optoelectronic device developed. High crystalline MAPbI3 nanowires were realized via methyl-ammonium iodide (MAI) vapor transfer treatment with PbI2 nanowires. PbI2 nanowires were prepared by a self-assembled procedure where PbI2 film was recrystallized and converted to nanowires structure with the exposure of dimethylacetamide (DMAC) vapor. On top of that, the density of MAPbI3 nanowires could be modulated by simply tuning the thickness of PbI2 film. The as-fabricated MAPbI3 nanowires photodetector exhibits a satisfying responsivity of 0.115 A W −1 @3 V while the rise time is less than 0.63 s and the decay time is less than 0.73 s. The study presents a bright future of MAPbI3 nanowires for optoelectronic application.